TEACHERS’ ROLE IN FOSTERING GLOBAL DIVERSITY CHARACTER: A CASE STUDY AT WARUGUNUNG PUBLIC ELEMENTARY SCHOOL REMBANG - Zulfah; Titik Haryati; Sumarno (SOSIOEDUKASI, 2025)
This study aims to explore the role of teachers in fostering global diversity character among students at SD Negeri Warugunung, Rembang. Using a qualitative descriptive approach with a case study design, data were collected through interviews, observation, and documentation involving teachers, the principal, and students. The findings reveal that teachers play a pivotal role in three dimensions: as educators, teachers internalize values of tolerance and empathy through modeling and habituation; as instructors, they integrate multicultural perspectives into classroom content, albeit inconsistently; and as trainers, they develop students’ intercultural competencies through collaborative and project-based learning activities. However, several limitations were identified, including the lack of structured curriculum planning, insufficient teacher training, and limited collaboration with external stakeholders. The novelty of this study lies in its comprehensive analysis of teachers’ multi-dimensional roles in shaping global citizenship character at the elementary level in a rural Indonesian context an area that remains under-researched. The study contributes valuable insights for education practitioners and policymakers in designing inclusive character education strategies that respond to the demands of 21st-century global competencies.